Analogia energii i kapitału - Dobija, Mieczysław (Capital and Energy: the Strong Analogy, 2005)
In economic language, economic power is called capital, although academics have not been fully aware of this connection. Capital, in its sense of being used to „do something", is analogous to a property in physical sense science that is labelled as „energy". Energy is often defined as „the capacity to do work". And thermodynamics is the field in which the applications of energy and heat are thoroughly studied. Thermodynamics provides us with a useful analogy for understanding capital. The second law of thermodynamics is a key to understanding the properties of energy and is used as a prime analogy for understanding capital and its theories. This approach to capital and value sheds new light on such economics and accounting topics as human capital, labour cost, the nature of the money unit, interest rates and discount rates.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 182-191